1977
DOI: 10.2337/diab.26.11.1016
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of “True” Glucose Production Rates in Infancy and Childhood with 6,6-Dideuteroglucose

Abstract: "New" glucose production has been measured in 54 infants and children for the first time by continuous three-to-four-hour influsion of the safe, nonradioactive tracer 6,6-dideuteroglucose. The use of combined gas chromatography--mass spectrometry with monitoring of selected ions allowed deuterium enrichment in blood glucose to be measured on microliter samples with an error of less than 2 per cent. In the young child, glucose production increased in a slightly curvilinear manner from 1 kg. to 25 kg. body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
144
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(153 citation statements)
references
References 0 publications
9
144
0
Order By: Relevance
“…Glucose production rates of the 3-to 5-year-old children with UFM in this study were comparable with the production rates in Kenyan children between 3 and 5 years of age in our previous study (29.6 lmol ⁄ kg ⁄ min, P = 0.072) (Dekker et al 1996). EGP in both the age groups was within the range of EGP in healthy children between 1 month and 6 years (Bier et al 1977;Haymond & Sunehag 1999). However, there are insufficient data in the literature to differentiate between children younger and older than 3 years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Glucose production rates of the 3-to 5-year-old children with UFM in this study were comparable with the production rates in Kenyan children between 3 and 5 years of age in our previous study (29.6 lmol ⁄ kg ⁄ min, P = 0.072) (Dekker et al 1996). EGP in both the age groups was within the range of EGP in healthy children between 1 month and 6 years (Bier et al 1977;Haymond & Sunehag 1999). However, there are insufficient data in the literature to differentiate between children younger and older than 3 years.…”
Section: Discussionsupporting
confidence: 88%
“…Age is generally considered an important determinant of EGP: glucose requirements in pre-term infants are approximately 44 lmol ⁄ kg ⁄ min (Van Kempen et al 2003), glucose production in term infants is approximately 33 lmol ⁄ kg ⁄ min and ranges between 27 and 43 lmol ⁄ kg ⁄ min in 1-month to 6-year-old children. Thereafter EGP decreases with age to 20 lmol ⁄ kg ⁄ min at the age of 8-10 years and 13 lmol ⁄ kg ⁄ min in adolescents (Bier et al 1977;Cowett et al 1983;Kalhan et al 1986;Haymond & Sunehag 1999;Sunehag et al 2001). Glucose production in children between 2.5 and 3.9 years with idiopathic ketotic hypoglycaemia ranged between 31.2 and 39.6 lmol ⁄ kg ⁄ min after an overnight fast (Huidekoper et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…When data are available concerning the human, they will also be discussed. (Bier et al, 1977). In keeping with this, it has been reported that in infants with a reduced cerebral mass (anencephaly or hydrancephaly), the glucose turnover rate per kg body-weight was similar to that of adults (Schwartz and Kahlan, 1975 (Shelley, 19611.…”
Section: Introductionmentioning
confidence: 55%
“…These two parameters have been measured in human (Gentz, Kellum and Persson, 1976 ;Kahlan et al, 1976 ;Bier et al, 1977) and rat (Chalk and Bailey, 1979 ;Ferré et al, 1980) and indicate that glucose supplied from the milk covers respectively 50 % and 20 % of the glucose requirements of the human and rat newborns. Thus gluconeogenesis is an essential process to maintain normoglycaemia in the breast-fed infant or suckling rat.…”
Section: Introductionmentioning
confidence: 95%
“…Provision of excess carbohydrate calories in PN can result in the development of SH. While normal infants and children may have substantially higher glucose turnover rates than adults, 81 limited data from critically ill children suggest that glucose infusion rates (GIR) less than 5 mg/kg/min may be optimal for glucose utilization from PN. 82,83 Further, BG concentrations may not accurately reflect glucose turnover and utilization.…”
Section: Prolonged Immobility and Stress Hyperglycemiamentioning
confidence: 99%